Application of Texture Analysis to Study Small Vessel Disease and Blood–Brain Barrier Integrity - Valdés Hernández, Maria del C.; González-Castro, Victor; Chappell, Francesca M.; Sakka, Eleni; Makin, Stephen; Armitage, Paul A.; Nailon, William H.; Wardlaw, Joanna M. (Frontiers in Neurology, 2017)
Objectives: We evaluate the alternative use of texture analysis for evaluating the role of blood-brain barrier (BBB) in small vessel disease (SVD). Methods: We used brain MRI from 204 stroke patients, acquired before and 20 minutes after intravenous gadolinium administration. We segmented tissues, white matter hyperintensities (WMH) and applied validated visual scores. We measured textural features in all tissues pre- and post-contrast and used ANCOVA to evaluate the effect of SVD indicators on the pre-/post-contrast change, Kruskal-Wallis for significance between patient groups and linear mixed models for pre-/post-contrast variations in cerebrospinal fluid (CSF) with Fazekas scores. Results: Textural ‘homogeneity’ increase in normal tissues with higher presence of SVD indicators was consistently more overt than in abnormal tissues. Textural 'homogeneity' increased with age, basal ganglia perivascular spaces scores (p<0.01) and SVD scores (p<0.05) and was significantly higher in hypertensive patients (p<0.002) and lacunar stroke (p=0.04). Hypertension (74% patients), WMH load (median=1.5±1.6% of intracranial volume) and age (mean=65.6 years, SD=11.3) predicted the pre-/post-contrast change in normal white matter, WMH and index stroke lesion. CSF signal increased with increasing SVD post-contrast. Conclusions: A consistent general pattern of increasing textural 'homogeneity' with increasing SVD, and post-contrast change in CSF with increasing WMH suggest that texture analysis may be useful for the study of BBB integrity.